Comparison of executive compensation practices at Nordic and US markets: a mini-review article based on empirical evidence - Ummeh Habiba Faria Benteh Rahman (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This paper examines the compensation package of the CEO of both the Nordic and US markets and their roles in the organization. The paper contains the comparison between the compensation package of Nordic and US CEOs along with the harmony of the determinants. The work pattern and compensation are different in these two markets, certainly. It has been a big influence in the organization or working places to provide the most desired efforts on the particular or assigned responsibilities. This study is based on a systematic review of literatures, empirical evidences and surveys extracted from 23 articles of the previous studies on the compensation packages of CEO of both Nordic and US markets. The paper will be discussing about the chief executive body in the organization, the compensation design along with their compensation package system, discussing about the theories and determinants’ differences of their compensation practices and how this package is designed in both the Nordic and US markets. The difference between these two markets will be elaborately discussed and following by the author’s own discussion. The paper will end by providing a valid conclusion about the whole study.